Patient preferences for treatments in hormone receptor-positive/HER2-negative metastatic breast cancer in Italy: a discrete choice experiment study - Grazia Arpino; Carmine De Angelis; Lorenzo Gerratana; Matteo Lambertini; Sarah Igidbashian; Rosanna Gramigna; Xavier Guillaume (BMC Cancer)
Abstract Hormone receptor (HR) positive (HR +) and human epidermal growth factor receptor 2 (HER2) negative (aka HER2 −) breast cancer (BC) is the most frequently diagnosed subtype. Recent development of next-generation endocrine therapies (e.g. selective estrogen receptor degraders (SERDs); third-generation aromatase inhibitors (AI) and targeted therapies (e.g., CDK4/6, PI3K, and mTOR inhibitors)) as well as antibody drugs conjugates (ADC, eg. T-DXd and SG) showed promising results with meaningful improvements in survival for patients with metastatic HR + HER2 − BC. Therapy selection is mainly based on clinical, tumor pathological and molecular characteristics as well as on efficacy based on trial data, nevertheless, side effect profiles are key differentiators of treatments in the metastatic setting. Therefore, understanding how patients evaluate various treatment attributes and how these change in different clinical situations is fundamental toward the choice of optimal therapeutic strategies for treating metastatic HR + HER2 − Stage IV patients. Here, we investigated treatment preferences of a total of 102 stage IV HR + HER2 − breast cancer patients in Italy by developing and applying a survey instrument based on discrete choice experiment (DCE). Treatment efficacy was the top valued attribute across all patient segments and the second most important attribute was the risk of grade ≥ 3 adverse events (AE). Overall, therapies with better outcomes of PFS or AE grade 3 or higher would have a higher impact on the preference to choose a treatment from a patient perspective.